Basic Concepts of Project Finance in PPP - Nalvarte Salvatierra, Pierre (2015)
Project Finance is an alternative financing mechanism to Corporate Finance which allows the companies to finance large infrastructure projects without endangers their own assets and heritage.Through Project Finance is possible to carry out major public works in the context of Public Private Partnership (PPP) Contracts, which the main guarantee of the creditors will be exploitation rights of the company that signs the public infrastructure contract, either by charging a fee to users (in case of self-sustaining PPP) or by charging a pre agreed amount to the State (in case of co-financed PPP).For a successful structuring of a PPP Project Finance, the joint work of a number of actors and legal instruments are required in order to complete the financing necessary circle in conditions of acceptable risk. The required actors are the Special Purpose Vehicle (SPV), the State, the Permitted Creditors, the Builder and Trustee. Among the necessary legal instruments include the PPP Contract, the Financing Contract, the Construction Contract and the Trust Agreement.